EFEKTIVITAS PENGGUNAAN MEDIA “SIP” UNTUK MENINGKATKAN KELANCARAN PROSEDURAL MATEMATIS SISWA KELAS II SEKOLAH DASAR - Anggita Zuniatu Zahrah; Babang Robandi; Rosiana Mufliva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Interactive Subtraction Reduction Media "SIP" is a learning media designed to address challenges in performing stacked subtraction calculations, both using borrowing techniques and without borrowing techniques, which are the main obstacles in subtraction operations. This study aims to identify the effectiveness of using "SIP" learning media to improve the procedural mathematical fluency of second-grade elementary school students. This research employs a quantitative method with a pre-experimental design, namely a one-group pre-test-post-test design. The sample of this study consists of 19 second-grade students. It uses test instruments (pre-test and post-test). The results indicate a significant improvement in the procedural mathematical fluency of students before and after the treatment. This is evidenced by the difference test of means using the Wilcoxon test and analysis of n-gain scores with the aid of SPSS statistics 27. The results of the Wilcoxon test showed a significance value of 0.001 < 0.05, which means H0 is rejected and Ha is accepted. In addition, the results of the n-gain test have a high effectiveness criteria. Therefore, it can be concluded that the use of the learning media 'SIP' is effective in improving the procedural mathematical fluency of second-grade elementary school students.